(untitled) (Gragoatá, 2018)
Resenha dos livros: BARBOSA, Francisco de Assis. A vida de Lima Barreto. 11ª ed. São Paulo ; Rio de Janeiro ; Belo Horizonte: Autêntica Editora, 2017. 432 p. SCHWARCZ, Lilia Moritz. Lima Barreto - triste visionário. São Paulo ; Rio de Janeiro: Companhia das Letras, 2018. 648 p. — DOI: http://dx.doi.org/10.22409/gragoata.2018n45a1034.